Acute coronary syndrome: how to reduce the residual inflammatory risk? - V. I. Shalnev (Российский кардиологический журнал)
Inflammatory mediators play an important role in the pathogenesis of acute coronary syndrome (ACS). The results of experimental and randomized clinical trials on the role of various inflammation inhibitors in the treatment of coronary artery disease (CAD), in particular CANTOS and COLCOT, mark a new stage that can significantly change the clinical course and outcomes of the disease. We analyze our own experience in studying this problem. There are much prospects for the use of immunomodulatory and anti-inflammatory drugs reducing the residual inflammatory risk, but additional studies are needed to determine their role in the treatment of CAD.